Contamination Issue in Viral Metagenomics: Problems, Solutions, and Clinical Perspectives - Jurasz, Henryk; Pawłowski, Tomasz; Perlejewski, Karol (Frontiers in Microbiology, 2021)
We describe the most common internal and external sources and types of contamination encountered in viral metagenomic studies and discuss their negative impact on sequencing results, particularly for low-biomass samples. We also propose some basic recommendations for reducing the background noise in viral shotgun metagenomic (SM) studies which would limit the bias introduced by various classes of contaminants. Regardless of the specific viral SM protocol, contamination cannot be totally avoided; in particular, the issue of reagent contamination should always be addressed with high priority. There is an urgent need for the development and validation of standards for viral metagenomic studies.